The Preliminary Results of 2021 and 2023 Egyptian Vulture Breeding Monitoring in Armenia - Lusine H. Aghadjanyan; Levon A. Harutyunyan (Пернатые хищники и их охрана)
The Egyptian Vulture (Neophron percnopterus) is one of the four breeding vulture species in Armenia. The most recent information on the status of the Egyptian Vulture population in Armenia can be found in the latest edition of the Red Data Book of the Republic of Armenia (2010), which reports the presence of 40–60 breeding pairs, including 10 in protected areas of Armenia.